2020
DOI: 10.5572/ajae.2020.14.4.422
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the National Air Pollutant Emission Inventory (CAPSS 2016) and the Major Cause of Change in Republic of Korea

Abstract: In 2016, air pollutant emissions in the Republic of Korea were 795,044 metric tons (hereafter tons) of CO, 1,248,309 tons of NOx, 358,951 tons of SOx, 611,539 tons of TSP, 233,085 tons of PM10, 100,247 tons of PM2.5, 16,401 tons of BC, 1,024,029 tons of VOCs, and 301,301 tons of NH3. Including energy production, thirteen emission sources, which comprise the national air pollutant emission inventory, were classified by their characteristics into five sectors (Energy, Industry, Road, Non-road, and Everyday Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…For areas outside of South Korea, the Northeast Asian emissions inventory contained within the KORUS v5 (Jang et al, 2020b) data was applied. For South Korea, the national emissions inventory named the Clean Air Policy Support System (CAPSS) 2016 (http://airemiss.nier.go.kr/mbshome/mbs/airemiss/index.do) was applied (Choi et al, 2020;Lee et al, 2011).…”
Section: Emission Sourcementioning
confidence: 99%
“…For areas outside of South Korea, the Northeast Asian emissions inventory contained within the KORUS v5 (Jang et al, 2020b) data was applied. For South Korea, the national emissions inventory named the Clean Air Policy Support System (CAPSS) 2016 (http://airemiss.nier.go.kr/mbshome/mbs/airemiss/index.do) was applied (Choi et al, 2020;Lee et al, 2011).…”
Section: Emission Sourcementioning
confidence: 99%
“…CAPSS 2016 (Choi et al 2020) and the Comprehensive Regional Emissions Inventory for Atmospheric Transport Experiment 2015 (CREATE 2015) (Jang et al 2019) were used as the emissions inventories, including EC for South Korea and Northeast countries. The spatial distribution of EC emissions used in this study is shown in Fig.…”
Section: Air Quality Simulationmentioning
confidence: 99%
“…In the Clean Air Policy Support System (CAPSS)-the national emissions inventory of South Korea-the amount of annual BC emissions in 2016 was approximately 16,000 tons. Among all emission source categories (defined as area, mobile, and point sources) in CAPSS 2016, the area source was the largest emission source category that accounted for approximately 59% of the total BC emissions in South Korea (Choi et al 2020;NAIR 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The simulation for South Korea was conducted for 2015-2019 using emissions from the Clean Air Policy Support System (CAPSS) 2016 [Choi et al, 2020] for South Korea and KORUSv5 [Woo et al, n.d] for outside South Korea. The simulation for North Korea was conducted for 2016 using emissions from the Comprehensive Regional Emissions Inventory for Atmospheric Transport Experiment (CREATE) 2015 [Woo et al, 2020] and CAPSS 2013.…”
Section: Regional Air Quality Model Evaluationmentioning
confidence: 99%